Analisis Kedisiplinan Anak Usia Dini Melalui Pembiasaan Di PAUD Baitul Marhamah - Samsiyah Samsiyah; Andriani Sariwardani; Amat Hidayat (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze early childhood discipline through habituation practices implemented at PAUD Baitul Marhamah. Discipline is a crucial component of character development in early childhood, and habituation serves as an effective method to instill consistent behavioral patterns. However, variations in children’s developmental conditions, parental involvement, and teacher consistency contribute to different outcomes in the development of discipline. This research employed a descriptive qualitative method using interviews, observations, and documentation. The participants included three children from group B, two teachers, and three parents. Data were analyzed to describe the habituation processes and the development of children’s discipline across three indicators: time discipline, rule discipline, and attitude discipline. The findings indicate that children’s levels of discipline vary and are influenced by parental involvement, individual developmental conditions, and teacher modeling. SM demonstrated strong and stable discipline, while AG and AH required additional guidance, particularly AH, who experiences speech delay that affects his ability to follow rules and instructions. A structured school environment and consistent routines, such as lining up, greeting, and cleaning up, significantly support the formation of disciplined behavior. This study concludes that habituation is an effective strategy for fostering discipline in early childhood; however, its success depends on the collaboration between teachers and parents as well as the alignment of habituation methods with the developmental characteristics of each child